Equilibrium Default Cycles - Kovrijnykh, Natalia; Szentes, Balázs (Journal of Political Economy, 2007)
This paper analyzes Markov equilibria in a model of strategic lending in which (i) agents cannot commit to long‐term contracts, (ii) contracts are incomplete, and (iii) incumbent lenders can coordinate their actions. Default cycles occur endogenously over time along every equilibrium path. After a sequence of bad shocks, the borrower in a competitive market accumulates debt so large that the incumbent lenders exercise monopoly power. Even though the incumbents could maintain this power forever, they find it profitable to let the borrower regain access to the competitive market after a sequence of good shocks. Equilibria are computed numerically, and their attributes are qualitatively consistent with numerous known empirical facts on sovereign lending. In addition, the model predicts that a borrower who accumulates debt overhang will regain access to the competitive credit market only after good shocks. This prediction is shown to be consistent with data on emerging market economies.